2023
DOI: 10.1186/s12877-023-03783-8
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum FT3 within the reference range is associated with mortality for older adults over 80 years of age with sarcopenia

Abstract: Objective Thyroid hormones stimulate myogenesis and muscle contraction and regulate skeletal muscle cell metabolism. However, the association between thyroid hormone levels and mortality in sarcopenic older adults remains elusive. The aim of this study was to investigate the relationship between thyroid hormones and all-cause mortality in people over 80 years of age with sarcopenia. Methods This study was performed on 264 sarcopenic patients aged 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…There are abundant studies associating thyroid-stimulating hormone (TSH) and free thyroxine (FT4) with mortality ( 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ). A Chinese study of 264 sarcopenic patients aged 80 years and older found that in a euthyroid population, those with lower levels of free triiodothyronine (FT3) had a higher risk of mortality ( 15 ). An American survey also found the association of ‘low–normal’ thyroid function and subclinical hypothyroidism with increased all-cause mortality ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are abundant studies associating thyroid-stimulating hormone (TSH) and free thyroxine (FT4) with mortality ( 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ). A Chinese study of 264 sarcopenic patients aged 80 years and older found that in a euthyroid population, those with lower levels of free triiodothyronine (FT3) had a higher risk of mortality ( 15 ). An American survey also found the association of ‘low–normal’ thyroid function and subclinical hypothyroidism with increased all-cause mortality ( 16 ).…”
Section: Introductionmentioning
confidence: 99%